The Milk Biochemical Parameters Having Economic Importance in Non-Dairy Acidosis Animals - CICEK, A. (Asian Journal of Chemistry, 2010)
This research was aimed to investigate the effect of acidosis on economic and non-economic biochemical components of milk in early lactation period. In the experiment, 10 acidosis and 10 healthy Karayaka ewes were used. The milk fat rate (economic) was lower for acidosis animals. Protein rates (economic) of milks were similar for both groups. There were statistically no significant differences between the groups for non-economic parameters (urea-N, Ca, P). There was found positive correlation between milk urea and protein (r = 0.52; p < 0.05), but there were no significant correlations among other economic and non-economic milk parameters. Prevention of acidosis and suitable rumen environment to increase production of milk with maximum levels of milk fat is essential for achieving the economic benefits.